GOVERNMENT COMMUNICATION: A CRITICAL ANALYSIS OF THE STRATEGIC DIMENSIONS OF THE CENTRAL NATIONAL GOVERNMENT COMMUNICATION IN KENYA - Owino, Ruth (International Journal of Communication and Public Relation, 2022)
Purpose: The purpose of this study is to critically analyze the strategic dimensions of the central national government communication in Kenya. The structure of the central national government communication is comprised of Presidential Strategic Communication Unit (PSCU), Office of the Government Spokesperson (OGS), and Ministry of information communication technology (ICT). Methodology: A single-case (embedded) research design was adopted and the target population was all the communication officers at the three government entities (PSCU, OGS, and Ministry of ICT). Data was collected through in-depth interviews and document analysis. Findings: The study findings indicate that the structure and process of government communicators are decentralized, uncoordinated, and adhoc. Communication is partly strategic and partly political. The professionals are mainly either recruited through political appointments, recommendations or recruited from civil service. Further, government communication is characterized by the pursuit of short/medium-term goals; strong political influence; limited specialized communication units; positioned at the lower level of the government structure; and considered a tactical tool that performs media and publicity functions. The study's findings are an important addition to the emerging field of government communication, especially on African scholarship where there is a serious dearth. Unique contribution to theory, practice and policy: Given the environment under which government communication operates, the findings of this study contribute to the excellence theory of public relations that advocates for excellent communication units. The findings are also helpful to policymakers and researchers since it provides a better understanding of government communication for possible improvement, regulation, and replication.